2012
DOI: 10.1073/pnas.1206785109
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Greenland’s mass loss in space and time

Abstract: The melting of polar ice sheets is a major contributor to global sea-level rise. Early estimates of the mass lost from the Greenland ice cap, based on satellite gravity data collected by the Gravity Recovery and Climate Experiment, have widely varied. Although the continentally and decadally averaged estimated trends have now more or less converged, to this date, there has been little clarity on the detailed spatial distribution of Greenland’s mass loss and how the geographical pattern has varied on relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 39 publications
7
89
1
Order By: Relevance
“…Again, the inland growth and coastal ablation was observed, with an epicenter in the southeast and increasing mass losses in the northwest. This spreading of the mass loss to the northwest (illustrated in Figure 20) was later confirmed in other studies [e.g., 203,204,205] and independently by GPS stations which recorded uplift of the Earth surface in response to the diminished ice load. In the same study, Khan et al [206] also reported moderate deceleration of the southeast ice loss in 2006 based on GRACE and GPS observations.…”
Section: Grace and The Cryosphere: Weighing The Icesupporting
confidence: 63%
“…Again, the inland growth and coastal ablation was observed, with an epicenter in the southeast and increasing mass losses in the northwest. This spreading of the mass loss to the northwest (illustrated in Figure 20) was later confirmed in other studies [e.g., 203,204,205] and independently by GPS stations which recorded uplift of the Earth surface in response to the diminished ice load. In the same study, Khan et al [206] also reported moderate deceleration of the southeast ice loss in 2006 based on GRACE and GPS observations.…”
Section: Grace and The Cryosphere: Weighing The Icesupporting
confidence: 63%
“…4). GRACE analyses suggest acceleration in mass loss in the NW since late 2005 or 2007 (Chen et al, 2011;Khan et al, 2010;Schrama and Wouters, 2011;Harig and Simons, 2012;Sasgen et al, 2012), with the highest mass loss rates at the end of the period, (i.e., since 2009). In contrast, Enderlin et al (2014) showed glaciers in the NW having a slowly increasing discharge over the period with a decrease in discharge acceleration during 2006-2008 and an increase in 2008-2010.…”
Section: Change In West Greenlandmentioning
confidence: 99%
“…Instead, these losses are inferred from satellite gravity anomalies (Chen et al, 2011;Harig and Simons, 2012;Luthcke et al, 2006;Ramillien et al, 2006;Velicogna and Wahr, 2005), remotely-sensed elevation changes at the ice sheet surface (Krabill et al, 2004;Pritchard et al, 2009) or surface mass balance models (Box et al, 2006;Van den Broeke et al, 2009a;Ettema et al, 2009;Fettweis, 2007;Hanna et al, 2008;Mernild et al, , 2010bVernon et al, 2013). All of these methods have uncertainties when used to estimate meltwater fluxes exiting the ice sheet.…”
Section: Introductionmentioning
confidence: 99%